Whole Genome Sequencing Analysis of African Orthobunyavirus Isolates Reveals Naturally Interspecies Segments Recombinations between Bunyamwera and Ngari Viruses - Moufid Mhamadi; Idrissa Dieng; Anna S. Dolgova; Cheikh Talibouya Touré; Mignane Ndiaye; Moussa Moïse Diagne; Babacar Faye; Anna S. Gladkikh; Vladimir G. Dedkov; Amadou Alpha Sall; Ousmane Faye; Oumar Faye (Viruses, 2023)
Bunyamwera virus is the prototype of the Bunyamwera serogroup, which belongs to the order Bunyavirales of the Orthobunyavirus genus in the Peribunyaviridae family. Bunyamwera is a negative-sense RNA virus composed of three segments S, M, and L. Genetic recombination is possible between members of this order as it is already documented. Additionally, it can lead to pathogenic or host range improvement, if it occurs with viruses of public health and agricultural importance such as Rift Valley fever virus and Crimea–Congo hemorrhagic fever virus. Here, we characterize five African Orthobunyavirus viruses from different geographical regions. Our results suggest that the five newly characterized strains are identified as Bunyamwera virus strains. Furthermore, two of the five strains sequenced in this study are recombinant strains, as fragments of their segments are carried by Ngari and Bunyamwera strains. Further investigations are needed to understand the functional impact of these recombinations.